Focused ultrasound-facilitated brain drug delivery using optimized nanodroplets: vaporization efficiency dictates large molecular delivery. (22nd January 2018) - Wu, Shih-Ying; Fix, Samantha M; Arena, Christopher B; Chen, Cherry C; Zheng, Wenlan; Olumolade, Oluyemi O; Papadopoulou, Virginie; Novell, Anthony; Dayton, Paul A; Konofagou, Elisa E
Abstract: Focused ultrasound with nanodroplets could facilitate localized drug delivery after vaporization with potentially improved in vivo stability, drug payload, and minimal interference outside of the focal zone compared with microbubbles. While the feasibility of blood–brain barrier (BBB) opening using nanodroplets has been previously reported, characterization of the associated delivery has not been achieved. It was hypothesized that the outcome of drug delivery was associated with the droplet's sensitivity to acoustic energy, and can be modulated with the boiling point of the liquid core. Therefore, in this study, octafluoropropane (OFP) and decafluorobutane (DFB) nanodroplets were used both in vitro for assessing their relative vaporization efficiency with high-speed microscopy, and in vivo for delivering molecules with a size relevant to proteins (40 kDa dextran) to the murine brain. It was found that at low pressures (300–450 kPa), OFP droplets vaporized into a greater number of microbubbles compared to DFB droplets at higher pressures (750–900 kPa) in the in vitro study. In the in vivo study, successful delivery was achieved with OFP droplets at 300 kPa and 450 kPa without evidence of cavitation damage using ¼ dosage, compared to DFB droplets at 900 kPa where histology indicated tissue damage due to inertial cavitation. In conclusion, the vaporization efficiency of nanodroplets positively impacted the amount of molecules delivered to the brain. The OFP droplets due to the higher vaporization efficiency served as better acoustic agents to deliver large molecules efficiently to the brain compared with the DFB droplets.